2020
DOI: 10.1186/s11671-020-3265-7
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive and Room Temperature CNTs/SnO2/CuO Sensor for H2S Gas Sensing Applications

Abstract: Gas sensors based on tin dioxide-carbon nanotube composite films were fabricated by a simple inexpensive sol-gel spin-coating method using PEG400 as a solvent. Nanostructured copper was coated on CNTs/SnO 2 film, and then copper was transformed into copper oxide at 250°C. Resistivity of the final composite films is highly sensitive to the presence of H 2 S, which became easily attached or detached at room temperature. The response and recovery time of the sensor are 4 min and 10 min, and the value of sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Like noble metal doping, the nanocomposites of MOS‐based sensing materials also lead to enhancing gas sensing performance. Heterojunction of MOS/MOS, [ 47,61,105,125,235,274–285 ] MOS/TMDs, [ 241–243,286 ] and MOS/carbon‐based materials [ 224,225,228,230,247,287–291 ] have been widely reported in the past few decades. In general, due to the different semiconducting properties, the sensing mechanism of heterojunctions and homojunctions is different.…”
Section: Strategies For Enhancement Of Gas Sensing Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Like noble metal doping, the nanocomposites of MOS‐based sensing materials also lead to enhancing gas sensing performance. Heterojunction of MOS/MOS, [ 47,61,105,125,235,274–285 ] MOS/TMDs, [ 241–243,286 ] and MOS/carbon‐based materials [ 224,225,228,230,247,287–291 ] have been widely reported in the past few decades. In general, due to the different semiconducting properties, the sensing mechanism of heterojunctions and homojunctions is different.…”
Section: Strategies For Enhancement Of Gas Sensing Performancementioning
confidence: 99%
“…CNTs that perform either metallic or semiconducting properties have also been used as sensing materials for decades. [ 41,288,307–310 ] Due to the different electronic property of CNTs and the theory which explained enhanced gas sensitivity of MOS‐based nanocomposites, the gas sensing performance of CNT‐MOS would be enhanced. Therefore, many researchers have tried to synthesize the composites of these CNT/graphene and MOS for demonstrating an enhanced gas sensing performance.…”
Section: Strategies For Enhancement Of Gas Sensing Performancementioning
confidence: 99%
“…As an important p-type semiconductor, cupric oxide (CuO) has been extensively studied to detect toxic and flammable gases owing to its non-toxicity, low cost and facile synthesis. 5,6 Kim et al reported a networked CuO nanowire grown on patterned-electrode pads by the thermal oxidation of Cu layers for detecting NO 2 gas, which displayed a gas-sensing response of about 55% towards 10 ppm NO 2 gas at an operational temperature of 300 1C, and a response time of 100 s and recovery time of 200 s were also recorded. 7 Navale et al designed CuO thin films on a quartz substrate using a simple and catalyst-free thermal evaporation technique for sensing NO 2 gas, exhibiting the maximum response value of 76% towards 100 ppm NO 2 gas at the operation temperature of 150 1C, and the LOD was only 1 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that CNTs play a major role as potential dopants of SnO 2 . Zhao et al 188 have synthesized CNTs/SnO 2 composite film using sol-gel followed by the CuO being coated by a vacuum evaporation method. The CNTs/SnO 2 /CuO film shows high sensitivity (S = R a À R c )/(DC = 4.41) and fast response and recovery times as compared to SnO 2 and SnO 2 /CuO nanocomposites.…”
Section: Carbon Nanotubesmentioning
confidence: 99%